Constitutionalisation of Civil Law: The fundamental right to contractual freedom, its scope and limits - Landa Arroyo, César (2014)
Constitutional Law has irradiated to the whole legal system, constitutionalizing Civil Law. However, it is also true that this process has occurred in reverse, “privatizing” Constitutional Law.In this article, the author presents us a complete analysis of the fundamental rights of private origin, with an special emphasis on the constitutional right to convene freely, its limits and its possible judicial control.